Pre‐clinical and Clinical Safety Studies of CMX‐2043: A Cytoprotective Lipoic Acid Analogue for Ischaemia–Reperfusion Injury. (16th May 2014) - Kates, Steven A.; Lader, Alan S.; Casale, Ralph; Beeuwkes, Reinier
Abstract CMX‐2043 is an α‐lipoic acid analogue targeted to reduction of cellular injury and organ damage due to ischaemia–reperfusion injury (IRI). It has been shown to be effective in a rat model of cardiac IRI. The studies here reported evaluate its safety and pharmacokinetic profile in preparation for human clinical studies in procedures associated with IRI. Safety and tolerability were tested in standard pre‐clinical in vitro and animal models and in a Phase 1 human clinical trial. CMX‐2043 did not bind to a wide range of receptors and specific targets at approximately 4 μg/mL (10 μM). It was not mutagenic by Ames assay, did not produce chromosome aberrations in Chinese hamster ovary (CHO) cells, and was negative for clastogenic potential. Toxicological studies in rats including both single and 14‐day repeat intravenous doses and in dogs (single intravenous dose) with a 2‐week recovery period were conducted. The NOAEL in rats and dogs was 30 and >10 mg/kg, respectively. No serious adverse events were reported in a placebo‐controlled, sequential dose escalation Phase 1 clinical trial. The low toxicity in the pre‐clinical studies and the absence of adverse events in the Phase 1 trial have supported investigation of CMX‐2043 in a human efficacy trial.